Parking management strategies for sustainable transportation: a case study for Istanbul - Barhani, Edison. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The rapid growth of the transportation sector during the last decade in Turkey has created many problems particularly in Istanbul such as air pollution, energy consumption, and loss of urban ‘living space’. Different from the traditional approach, where supply is always provided to meet demand, the sustainable transportation is environmentally sensible, society fair, and economically sound. Therefore, the need for a detailed and comprehensive transport policy, to encourage sustainable transport, is essential for Istanbul. One of the most crucial transportation management strategies that can be regarded to achieve more sustainable transportation system is parking management. The objective of this research was to study the nature and level of the parking problem and to recommend some applicable parking management strategies for Istanbul. In order to accomplish this, analysis of “Istanbul Origin-Destination Travel Questionnaire” data and a license plate survey for the selected pilot study area were performed. Next, two parking management strategies, parking pricing and parking duration limitation, were decided for the pilot study area. The results of the analysis showed that 13% of the on-street parking demand could be decreased due to parking pricing and 15% reduction could be attributed to the parking duration limitation strategy. Beside the ones mentioned above some other recommended parking management strategies for Istanbul metropolitan area were: shared parking, parking regulation, unbundled parking, financial incentives, parking impact fees, increasing the price of parking based on a tax on revenues and/or parking spaces, and combinations of the above strategies.
Keywords: Transportation -- Planning.; Parking facilities.; Automobile parking.